2019
DOI: 10.1111/imcb.12225
|View full text |Cite
|
Sign up to set email alerts
|

The R132H mutation in IDH1 promotes the recruitment of NK cells through CX3CL1/CX3CR1 chemotaxis and is correlated with a better prognosis in gliomas

Abstract: Mutations in the isocitrate dehydrogenase (IDH) 1 gene, especially the R132H mutation, have been reported to be associated with a better prognosis in glioma patients. However, the underlying molecular mechanisms are not yet well understood. Many factors may contribute to differences in the survival of IDH1 wild‐type and IDH1 mutant glioma patients, in which immune components play a potentially important role. In this study, we analyzed The Cancer Genome Atlas (TCGA), and the Chinese Glioma Genome Atlas (CGGA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 54 publications
(84 reference statements)
1
21
0
Order By: Relevance
“…We found that incubation VMECs with CX3CL1 significantly increased the migration rate of cancer cells and that inhibiting Src/P115-RhoGEF/ROCK signaling in VEMCs effectively blocked the process of tumor cell TEM. These data together with the results of previous studies (Furio et al, 2018;Ren et al, 2019) indicated that in addition to their roles in chemotaxis and adhesion, CX3CL1mediated VMECs barrier disruption and subsequent vertebral micro-vascular hyper-permeability also play key roles in cancer cell TEM in the spine.…”
Section: Discussionsupporting
confidence: 78%
“…We found that incubation VMECs with CX3CL1 significantly increased the migration rate of cancer cells and that inhibiting Src/P115-RhoGEF/ROCK signaling in VEMCs effectively blocked the process of tumor cell TEM. These data together with the results of previous studies (Furio et al, 2018;Ren et al, 2019) indicated that in addition to their roles in chemotaxis and adhesion, CX3CL1mediated VMECs barrier disruption and subsequent vertebral micro-vascular hyper-permeability also play key roles in cancer cell TEM in the spine.…”
Section: Discussionsupporting
confidence: 78%
“…Several computational-based studies show that glioma patients expressing activated NK cell transcriptional signatures (TS) have improved prognosis (2,(25)(26)(27)(28)(29). Studies in patients and mouse models support these findings (10,30,31), with one human study showing a remarkable relationship between the presence of activated NK cells and improved survival in GBM (32). Another study showed that activated NK cells were higher in low grade compared to high grade gliomas suggesting reduction in activated NK cells is associated with transition from low to high grade brain cancers (27).…”
Section: Nk Cells In Brain Cancermentioning
confidence: 88%
“…Sevoflurane was also reported to attenuate NK cell–mediated cytotoxicity by inhibiting adhesion molecule leukocyte function-associated antigen-1 in an experimental study 45 . The importance of NK cells for glioma outcomes has been recently addressed; the IDH1 R132 mutation promotes recruitment of NK cells in the brain and is associated with improved glioma prognosis 46 . In addition, novel therapies based on augmentation of NK cell recruitment and function are emerging in neuro-oncology 47 .…”
Section: Discussionmentioning
confidence: 99%